Factors effecting the cost management in construction projects - Albtoush, Faten Ahmad; Doh, Shu Ing; A. R., Rahimi; Albtoush, Ja'far A. Aldiabat (IAEME Publication, 2020)
Cost management is an important stage in construction project life cycle, construction projects need cost management in the first stage to finish the project within required cost, time and quality, it's considered as the most factors affecting in the success of construction projects in all developing and developed countries. Many researchers focused to studying the factors affected in cost performance in construction projects in different countries, because cost is an important attribute in construction projects. The project considered as success project when it finished within limited cost and time with required quality, the three items (cost, time and quality) depend on each other, any change in one of them affects the other, whether the effect was positive or negative, the main item of them is cost, so this encourage many researchers to study the factors affected in cost management. This research is carried out to highlight the information on the factors that affected in cost management during the life cycle on construction project, the data collected through 41 reviews focused in studying factors affected in cost performance of construction project. In this research it is to be found different factors in different countries and different projects, the most important factors found through literature review are: design changes, poor management in the site, delay in progress payment by owner, fluctuation in material price.